Innovation In Environmental Policy Of Community-Based Waste Management In Achieving A Low-Carbon City - Subhan; Tjenreng, Zubakhrum (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Study. This aim is to analyze the implementation of innovation management in a rubbish-based community to support achieving the Low Carbon City in Bogor Regency and study inequality between policy macro and conditions in the field. Although the National Policy and Strategy for Management of Garbage (Jakstranas) targets a 75% reduction in rubbish to 75%, realization in Bogor Regency is still in the range of 44%. This is caused by structural obstacles like TPST/TPAS infrastructure limitations, lack of transport fleet, and not yet optimal regulations and zoning. Research This study uses cases in three subdistricts (Cibinong, Bojonggede, and Cileungsi), and found that innovation communities, such as digital waste banks, maggot composting, and eco enzymes, are capable of reducing organic waste volume by 20–30% and increasing sorting up to 35%. Projection impact on emission shows that if innovation is replicated all over House households in Bogor Regency (±600 thousand), then potential subtraction of GHG emissions can reach 48,000–72,000 tons of CO₂-e / year. Research This produces an integrative model for managing rubbish based on a community that can support the reduction of emissions concretely and strategically to realize a low-carbon city. Findings: This confirms the importance of multi-actor synergy and supports policy adaptive areas​ to initiate locally.